2012
DOI: 10.1007/s10620-012-2039-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Full-Thickness Resection of Submucosal Gastric Tumors

Abstract: Gastric EFTR using the novel EFTR prototype device is feasible in a live animal model. The technique can achieve a full-thickness gastric wall and submucosal tumor resection with reliable closure of the gastric wall, but further refinements of the technique and device are necessary in order to reliably resect submucosal lesions, especially larger ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Thereafter, one of the tumors was removed endoscopically using a novel prototype for endoscopic fullthickness-resection (FTRD, full-thickness-resection device; Ovesco Endoscopy AG, Tuebingen, Germany) [12].…”
Section: Diagnostic and Therapeutic Routesmentioning
confidence: 99%
“…Thereafter, one of the tumors was removed endoscopically using a novel prototype for endoscopic fullthickness-resection (FTRD, full-thickness-resection device; Ovesco Endoscopy AG, Tuebingen, Germany) [12].…”
Section: Diagnostic and Therapeutic Routesmentioning
confidence: 99%
“…En-bloc resection is widely performed for the treatment of definite GISTs. Currently, minimally invasive local resection techniques, such as hybrid natural orifice transluminal endoscopic surgery (NOTES), which consists of endoscopic full-thickness resection (EFTR), have been developed for the treatment of endoluminal GISTs (2,3). Furthermore, endoscopic diagnostic methods for SETs have been proposed (4,5), including our safe and reliable method of bloc biopsy performed under a direct endoscopic view by using submucosal endoscopy with a mucosal flap method (SEMF) (4).…”
Section: Introductionmentioning
confidence: 99%
“…The latest National Comprehensive Cancer Network (NCCN) task force report has suggested that all GISTs 2 cm or larger should be resected [3]. With the progressive increase in experience in endoscopic submucosal dissection (ESD), endoscopic full-thickness resection (EFTR) without laparoscopic assistance has been applied to remove GISTs with extra-luminal growth and/or close proximity to the serosa [4][5][6][7][8][9]. The key step of the EFTR procedure is the complete closure of wall defects left by full-thickness resection and thereby avoiding surgical intervention.…”
mentioning
confidence: 99%